1989
DOI: 10.1103/physrevb.39.8059
|View full text |Cite
|
Sign up to set email alerts
|

Negative magnetoresistance in the variable-range-hopping regime inn-type GaAs

Abstract: Low-field magnetoresistance measurements for compensated, n-type three-dimensional GaAs with net donor concentration just below the metal-insulator transition show a quadratic field dependence for values of 8 less than 750 G. Temperature-dependent measurements in zero 6eldshow that transport is by variable-range hopping, and are consistent with the presence of a Coulomb gap which narrows close to the transition. It is found that the temperature dependence of the eff'ective area in which the Aux is enclosed is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
29
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(34 citation statements)
references
References 13 publications
4
29
1
Order By: Relevance
“…We observed that the curve obtained can be adjusted by a straight line that gives us the following law: ). This behaviour is similar to those obtained by Trembey [18] and Capoen [31] on GaAs samples, Zhang and Sarachik [19] on CdSe samples. These authors found that ) ( 1 T f has the same variation with temperature, regardless of the impurities concentration of samples and of the regime of conduction observed.…”
Section: Results Discussion and Conclusionsupporting
confidence: 78%
See 2 more Smart Citations
“…We observed that the curve obtained can be adjusted by a straight line that gives us the following law: ). This behaviour is similar to those obtained by Trembey [18] and Capoen [31] on GaAs samples, Zhang and Sarachik [19] on CdSe samples. These authors found that ) ( 1 T f has the same variation with temperature, regardless of the impurities concentration of samples and of the regime of conduction observed.…”
Section: Results Discussion and Conclusionsupporting
confidence: 78%
“…We observed that in the limit of low fields, the NMR varies linearly with 2 B and the slopes ) ( 1 T f of these straight lines decrease when the temperature increases. We also noticed that the value of magnetic field m B , from which the linearity deviation occurs increases with temperature, which is good agreement with the theory proposed by Entin-Wohlman [18]. The NMR has been adjusted using the following form:…”
Section: Results Discussion and Conclusionsupporting
confidence: 71%
See 1 more Smart Citation
“…This was attributed [10,12] to hopping energies that were larger than the gap energy at high temperature (Mott hopping) and smaller than the gap at low T (ES hopping). A crossover with dopant concentration was found in n-GaAs [13], where Mott hopping was claimed for samples near the metal-insulator transition when the Coulomb gap has a small energy-width, and ES hopping prevails deeper in the insulating phase where electron-electron interactions are stronger and the hopping electrons probe the gap. Although variable-range hopping exponents have been found that deviate from these values, it is found that strong electron interactions yield a hopping exponent of 1/2 while weak interactions (compared with hopping energies) give rise to exponent 1/4.…”
mentioning
confidence: 97%
“…Although variable-range hopping exponents have been found that deviate from these values, it is found that strong electron interactions yield a hopping exponent of 1/2 while weak interactions (compared with hopping energies) give rise to exponent 1/4. This has given rise to the expectation that Mott variable-range hopping will always be observed near the metal-insulator transition as electron screening increases and the Coulomb gap collapses approaching the metallic phase [13,14].…”
mentioning
confidence: 98%